Peran Perpustakaan di Era Digital Dalam Penguatan Akses Informasi - Muhammad Fariz Anaan; Lisa Agustina Soraya; Herlina (Jurnal Gema Pustakawan, 2025)
A library is a part of an educational establishment that supports learning, research, and publications by offering different types of information in accordance with user needs. Users nowadays have undergone a drastic transformation along with the quick growth of information and communications technologies. Starting with their Internet-based information-seeking habits, how they pick up knowledge while playing games or listening to music, and how much fun they have working together and exchanging information online. The term "digital generation" is used to describe them. Digital libraries play a strategic role in strengthening community access to information through the provision of easily accessible and accurate digital information services. Research findings indicate that digital libraries can overcome time and space limitations in accessing information and contribute to the empowerment of digital literacy. Challenges such as infrastructure and human resource competencies need to be addressed to optimize this role.